PENGARUH PEMBERIAN INSENTIF DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN DIVISI TIGA PADA PT. ABDI BUDI MULIA TELUK PANJI LABUHAN BATU SELATAN SUMATERA UTARA - Mely Rahmilawati; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
An important problem faced by leaders is how to increase morale so that they can support the success of achieving goals. Trying to maintain the enthusiasm of employees so they can work hard. This research was conducted at PT. Abdi Budi Mulia Teluk Panji , South Labuhan Batu, North Sumatra. This study aims to determine and analyze the effect of incentives and the work environment on employee morale partially and simultaneously. Providing incentives (X1) and work environment (X2) as independent variables and work enthusiasm (Y) as the dependent variable. The problem in this study is the fluactive decline in employee morale accompanied by high employee absenteeism. Seen from the absence of the company. The sample for this research was taken as many as the number of employees of the third division, namely 60 respondents and the technique used was a census. Data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS program. From the results of the tests carried out, it was found that the provision of incentives and the work environment had a positive and significant effect on the morale of employees of PT. Abdi Budi Mulia Division three Teluk Panji, Labuhan Batu south, North Sumatra. Keywords: Providing Incentives, Work Environment, Employee Enthusiasm